Female judo athletes` physical test performances are unrelated to technical-tactical competition skills - Kons, R. L.; Dal Pupo, J.; Ache-Dias, J.; Detanico, D. (Perceptual and Motor Skills, 2018)
This study analyzed the relationship between generic and judo-specific physical test performances and technical-tactical competition performances among 19 female judo athletes. Participant data were gathered in two stages: (a) physical tests—countermovement jump (CMJ), handgrip strength, Special Judo Fitness Test and Judogi Grip Strength Test; and (b) match performances recorded for technical-tactical analysis. Pearson`s linear correlation and multiple linear regression analysis showed no significant correlations between any technical-tactical parameter and judo-specific physical tests. However, the number of attacks during matches was significantly positively correlated with countermovement jump height (CMJJH; r = 0.69, p = .002), peak power output (CMJPPO; r = 0.53, p = .002), and peak velocity (CMJPV; r = 0.62, p = .001). Effective time during matches was significantly correlated with all CMJ parameters (except maximum force; r = 0.65-0.76, p = .01) and with right hand grip strength (r = 0.48, p = .037). Match effectiveness was correlated with CMJPPO (r = -0.67, p = .001), mean power output (CMJMPO; r = -0.54, p = .017), and CMJPV (r = -0.54, p = .004). The explained power of variance was low for all variables at 45-54%. We conclude that judo-specific performance tests do not seem to be related to female judo athletes` technical-tactical skills in official competition, though athletes with higher lower limb muscle power and higher handgrip strength showed higher time effectiveness during matches.